IκBNS expression in B cells is dispensable for IgG responses to T cell-dependent antigens - Khoenkhoen, Sharesta; Ádori, Monika; Solís-Sayago, Darío; Soulier, Juliette; Russell, Jamie; Beutler, Bruce; Pedersen, Gabriel K.; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2022)
Mice lacking the atypical inhibitory kappa B (IκB) protein, IκBNS, a regulator of the NF-κB pathway encoded by the nfkbid gene, display impaired antibody responses to both T cell-independent (TI) and T cell-dependent (TD) antigens. To better understand the basis of these defects, we crossed mice carrying floxed nfkbid alleles with mice expressing Cre under the transcriptional control of the Cd79a gene to create mice that lacked IκBNS expression only in B cells. Analyses of these conditional knock-out mice revealed intact CD4+ and CD8+ T cell populations, including preserved frequencies of FoxP3+ regulatory T cells, which are known to be reduced in IκBNS knock-out mice. Like IκBNS knock-out mice, mice with conditional IκBNS ablation in B cells displayed defective IgM responses to TI antigens and a severe reduction in peritoneal B-1a cells. However, in contrast to mice lacking IκBNS altogether, the conditional IκBNS knock-out mice responded well to TD antigens compared to the control mice, with potent IgG responses following immunization with the viral antigen, rSFV-βGal or the widely used hapten-protein model antigen, NP-CGG. Furthermore, B cell intrinsic IκBNS expression was dispensable for germinal center (GC) formation and T follicular helper cell responses to NP-CGG immunization. The results presented here suggest that the defect in antibody responses to TD antigens observed in IκBNS knock-out mice results from a B cell extrinsic defect.